Effects of Different Drying Methods on the Retention of Bioactive Compounds, On-Line Antioxidant Capacity and Color of the Novel Snack from Red-Fleshed Apples - Wojdyło, Aneta (Molecules, 2020)
The aim of this study was to determine the effect of different drying methods: convective (at 50, 60, 70 °C), vacuum-microwave (at 120, 240, 360, 480 W and 360 W with reduction to 120 W) and hybrid (convective pre-drying at 50, 60, 70 °C followed by vacuum-microwave drying at 120 W) on the quality parameters of novel red-fleshed apple fruit snacks (RFAs), such as phenolics, on-line antioxidant capacity, water activity and color. Drying kinetics, including a temperature profile of dried material, and modified Page model were determined. Freeze-drying was used as a control method. The highest content of bioactive compounds in the samples was retained following freeze-drying, then hybrid, vacuum-microwave and finally convection drying. The antioxidant capacity measured by on-line 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS), identified anthocyanins, flavan-3-ols and phenolic acid as the main compounds responsible for this activity. Unfavorable changes in color, formation of hydroxymethylfurfural (HMF) and degradation of polyphenolics were noted along with increasing drying temperature and magnetron power. The red-fleshed apple snacks are a promising high-quality dehydrated food product belonging to functional foods category.